A systematic observation of vasodynamics from different segments along the cerebral vasculature in the penumbra zone of awake mice following cerebral ischemia and recanalization. Issue 5 (May 2023) - Qiu, Baoshan; Zhao, Zichen; Wang, Nan; Feng, Ziyan; Chen, Xing-jun; Chen, Weiqi; Sun, Wenzhi; Ge, Woo-ping; Wang, Yilong
Different segments of the cerebral vascular network may react distinctly to brain ischemia and recanalization. However, there are limited systematic observations of these vascular responses in mice under a physiological state following ischemic stroke. Herein, we aimed to investigate the vasodynamics among several segments along the cerebral vessels in awake mice following cerebral ischemia/recanalization via two-photon imaging. Plasma in the blood vessels were labelled with fluorescein isothiocyanate dextran. Smooth muscle cells and pericytes were labelled via a genetic mouse line (PDGFRβ-tdTomato). We observed a no-reflow phenomenon in downstream microcirculation, and the vasodynamics of different segments of larger cerebral vessels varied in the penumbra area following cerebral ischemia-reperfusion. Despite obtaining reperfusion from the middle cerebral artery, there were significant constrictions of the downstream blood vessels in the ischemic penumbra zone. Interestingly, we observed an extensive constriction of the capillaries 3 hours following recanalization, both at the site covered by pericyte soma and by the pericyte process alone. In addition, we did not observe a significant positive correlation between the changed capillary diameter and pericyte coverage along the capillary. Taken together, abnormal constrictions and vasodynamics of cerebral large and small vessels may directly contribute to microcirculation failure following recanalization in ischemic stroke.